The Effect Of The Problem Based Learning Model With The Inquiry Method On The Mathematical Problem Solving Ability Of Grade V Students - Amelia Hardiwa; Supriadi Supriadi; Erwin Nurdiansyah (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This study conducted on May 19, 2025, aims to determine the effect of using the Problem-Based Learning model with the Inquiry method on students mathematical problem-solving abilities. Lack of interest, difficulty understanding the material and students unwillingness to ask questions caused 29.16% of students to have daily mathematics test scores below the minimum passing grade. This study used a quantitative approach with a pre-experimental method (one group pre-test and post-test design), purposive sampling technique, and instruments in the form of observation sheets, tests, and documentation. The results showed that the application of the Problem-Based Learning Model with the Inquiry Method succeeded in creating an active, collaborative, and student-centered learning atmosphere, thereby motivating students to engage in real-world problem solving. The test results showed a significant increase in the average post-test score of students to 88.83 compared to the pre-test score of 69.33. These results prove that the collaboration of these two approaches is very effective in optimizing students conceptual understanding and critical thinking skills at the elementary education level.